2010
DOI: 10.1177/1091581809357082
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids, XI: Pharmacokinetic and Tissue Distribution Study of 14C-Dihydrocapsiate and Metabolites in Rats

Abstract: Pharmacokinetics of a single gavage dose of (14)C-labeled dihydrocapsiate (10 mg/kg) were investigated in male rats. Maximal plasma concentration was achieved in 40 minutes and exhibited an apparent half-life of 2.4 hours. Excretion of radioactivity in the urine, feces, and expired air was 78.2%, 19.4%, and 0.5% of the dose, respectively. Highest tissue concentrations were achieved in the kidney, liver, and blood; the data indicate that radioactivity accumulation following daily exposure at a dose of 10 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Similar results have been obtained while studying glucuronide formation of 4-nitrophenol under the same experimental conditions [38]. Although hepatic metabolism of the two capsaicinoids has been demonstrated [13][14][15] M a n u s c r i p t …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been obtained while studying glucuronide formation of 4-nitrophenol under the same experimental conditions [38]. Although hepatic metabolism of the two capsaicinoids has been demonstrated [13][14][15] M a n u s c r i p t …”
Section: Discussionsupporting
confidence: 87%
“…Structural characteristics of capsaicinoids are responsible for their spicy flavor and biological activities are associated with the presence of an amide bond connecting a vanillyl ring and an acyl chain [1]. Experiments with (14)C-labeled capsaicinoids showed the compounds to have comparable pharmacodynamic and pharmacokinetic properties [13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…There are only a few studies that have examined the pharmokinetics and bioavailability capsaicin, most of which have been carried out in rats . In humans, capsaicin is generally assessed through the consumption of chilli peppers and related spices : One study have reported serum concentrations of 8.1 nM after oral consumption of 5 g of chilli peppers, whereas other studies have reported a concentrations ranging from 13.4–16.3 ng/ml after the consumption of chilli‐containing meal .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining how capsaicin may be altering these enzymes may be of relevance for developing therapeutic strategies for preventing the progression of neuroendocrine and castrate-resistant tumors [30]. There are only a few studies that have examined the pharmokinetics and bioavailability capsaicin, most of which have been carried out in rats [31][32][33]. In humans, capsaicin is generally assessed through the consumption of chilli peppers and related spices [34]: One study have reported serum concentrations of 8.1 nM after oral consumption of 5 g of chilli peppers, whereas other studies have reported a concentrations ranging from 13.4-16.3 ng/ml after the consumption of chilli-containing meal [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Capsiate is an equipotent capsaicin analog that was identified in a much less pungent chili pepper cultivar, CH-19 sweet (22), and has an ester bond in its structure in place of the amide bond in capsaicin, making it highly vulnerable in the digestive system. Use of this TRP channel ligand, therefore, enables us to evaluate the effect of selective stimulation of TRP channels in the GI tract without affecting those in other sensory systems (5,6,54). Here, we show that selective activation of TRP channels, presumably the TRPV1 type, located in the upper GI tract is sufficient to trigger the thermogenic reflex through the intermediary step of activating vagal afferents and sympathetic efferents innervating the BAT.…”
mentioning
confidence: 79%